Efektivitas Kombinasi Ekstak Buah Merah (Pandanus Conoideus Lam) Dan Air Kelapa Hijau Terhadap Kualitas Semen Sapi Bali Selama Simpan Dingin - Ervandi, Mohamad; Makoolang, Susan; Ardiansyah, Widiastuti; Suci Ananda (Jurnal Ilmu dan Industri Peternakan, 2023)
The purpose of this study was to determine the effectiveness of the combination of red fruit extract (pandanus conoideus lam) and green coconut water on the quality of Balinese cattle semen during cold storage. This research was conducted at the Field Laboratory of the Animal Husbandry Study Program, Faculty of Science and Technology. The method used was experimental laboratory. Semen used came from 2 Balinese cows aged 2-3 years collected 1 week 2 times. The research design used a Randomized Group Design (RAK) with 4 conditions and 10 repetitions consisting of P0 (control) = CEP-2 + 10% egg yolk, P1 = diluent of red fruit extract + coconut water + 10% egg yolk. P2 = red fruit extract diluent + coconut water + egg yolk 10% + fructose 1 mg/ml. P3 = red fruit extract diluent + coconut water + egg yolk 10% + fructose 2 mg/ml. The data generated will be analyzed using Analysis of Variance. The results showed that the best motility and viability in P0 (42.41 ± 1.72%) and (40.10 ± 1.12%) and low abnormality <10% which lasted until the 8th day of storage, then followed by P2 (43.19 ± 1.34%) and (47.22 ± 1.12%) and abnormality below <14%. After that followed by P1 (42.26 ± 1.40%) and (45.28 ± 1.19) and P3 (42.16 ± 1.37%) and (43.44 ± 1.17%) each P1 and P3 had abnormalities below <14%. In conclusion, the three diluents P1, P2 and P3 were able to maintain motility, viability and abnormality until the 5th day after storage so that the use of a combination of red fruit extract and coconut water in liquid semen can be used for the implementation of IB in the field.